How Members of Parliament understand and respond to climate change - Willis, Rebecca (The Sociological review (Keele))
Action on climate change, to meet the targets set in the 2015 Paris Agreement, requires strong political support at the national level. Whilst the political and governance challenges of climate change have been discussed at length, there is little understanding of how politicians, as influential individuals within the political system, understand or respond to climate change. This article presents findings from 14 qualitative interviews with Members of the UK Parliament, to discuss how politicians conceptualise climate change, and their deliberations on whether or how to act on the issue. First, it reviews an interdisciplinary literature from sociology, political theory and science and technology studies, to investigate how politicians navigate their work and life. Second, it presents ‘composite narratives’ to provide four different MPs’ stories. Last, it draws conclusions and implications for practice. It highlights three crucial factors: identity, or how politicians consider the climate issue in the context of their professional identity and the cultural norms of their workplace; representation, how politicians assess their role as a representative, and whether proposed political action on climate is seen as compatible with this representative function; and working practices, how day-to-day work rituals and pressures influence the aims, ambitions and engagement of politicians with climate change.